1999
DOI: 10.1074/jbc.274.50.35514
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Flavinylation Is Essential for Efficient Redox Catalysis in Vanillyl-alcohol Oxidase

Abstract: By mutating the target residue of covalent flavinylation in vanillyl-alcohol oxidase, the functional role of the histidyl-FAD bond was studied. Three His 422 mutants (H422A, H422T, and H422C) were purified, which all contained tightly but noncovalently bound FAD. Steady state kinetics revealed that the mutants have retained enzyme activity, although the turnover rates have decreased by 1 order of magnitude. Stopped-flow analysis showed that the H422A mutant is still able to form a stable binary complex of redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
154
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 118 publications
(176 citation statements)
references
References 48 publications
21
154
0
1
Order By: Relevance
“…Previous studies have indicated that the covalent interaction between His-422 and the isoalloxazine ring markedly increases the redox potential of the flavin cofactor (10). The redox potentials of D170A͞T457E and D170S͞T457E were only slightly lower than that of wild-type VAO, supporting the proposal that an acidic residue in the active site cavity is required for maintaining the high redox potential (11).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous studies have indicated that the covalent interaction between His-422 and the isoalloxazine ring markedly increases the redox potential of the flavin cofactor (10). The redox potentials of D170A͞T457E and D170S͞T457E were only slightly lower than that of wild-type VAO, supporting the proposal that an acidic residue in the active site cavity is required for maintaining the high redox potential (11).…”
Section: Discussionsupporting
confidence: 60%
“…The inhibitor was clearly visible in the electron density map of one of the two crystallographically independent subunits (subunit B). Its orientation in the proximity of the flavin ring was nearly identical to the orientation in several previously determined enzymeinhibitor complex structures (8,10,11). Superposition of the structures of trifluoromethylphenol-complexed D170S͞T457E and isoeugenol-complexed wild-type VAO (8) showed that the two amino acid replacements did not cause any significant conformational change, which is reflected in a rms deviation for all C␣-atoms of only 0.23 Å.…”
Section: Stereochemistry Of the Mutant Enzymesmentioning
confidence: 72%
See 2 more Smart Citations
“…This is similar to plant GALDHs, where leucine is found at this site, leading to the suggestion that plant enzymes may interact noncovalently with FAD (28,29). In the related flavoprotein vanillyl-alcohol oxidase (VAO), the equivalent histidine facilitates flavinylation at a second histidine residue near the C terminus (30). This second histidine is conserved at a corresponding position in all GLO͞ALO͞GALDH sequences reported (residue 462 in TbALO) (Fig.…”
Section: Resultsmentioning
confidence: 90%